2021
DOI: 10.1037/edu0000623
|View full text |Cite
|
Sign up to set email alerts
|

The effects of knowledge activation training on rural middle-school students’ expository text comprehension: A mixed-methods study.

Abstract: The purpose of the current mixed-methods study was to investigate the effectiveness of a traditional and novel knowledge activation technique for supporting fifth and sixth graders' comprehension of exposition covering unfamiliar content. For the quantitative portion, 149 rural middle-school students were randomly assigned to 1 of 3 conditions: knowledge mobilization (traditional), relational reasoning (novel), or text annotation (control). Readings used during training and for posttraining assessment were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Probing questions can guide students to recognize analogies (similarities), anomalies (discrepancies), antinomies (exclusivities), and antitheses (opposites) between what students already know and textual information. As a knowledge activation technique, relational reasoning questions can guide students before, during, and after reading to gauge how their prior topic, domain, or personal knowledge does or does not fit with the textual content (Hattan & Alexander, in press).…”
Section: Activating Integrating and Revising Knowledge Throughout The Reading Processmentioning
confidence: 99%
“…Probing questions can guide students to recognize analogies (similarities), anomalies (discrepancies), antinomies (exclusivities), and antitheses (opposites) between what students already know and textual information. As a knowledge activation technique, relational reasoning questions can guide students before, during, and after reading to gauge how their prior topic, domain, or personal knowledge does or does not fit with the textual content (Hattan & Alexander, in press).…”
Section: Activating Integrating and Revising Knowledge Throughout The Reading Processmentioning
confidence: 99%
“…Two studies compared strategic or procedural supports to knowledge mobilization. Wetzels et al (2011b) found benefits for both perspective taking and mobilization, while Hattan & Alexander (2021) only found benefits for relational reasoning.…”
Section: Procedural or Strategic Supports During Text Processingmentioning
confidence: 93%
“…Within the reviewed literature, individual differences, such as grade level or amount of prior knowledge, influenced the effectiveness of knowledge activation techniques. For example, younger students seemed to benefit from more structured knowledge activation prompts, as opposed to open-ended scaffolds (e.g., Gurlitt & Renkl, 2008;Hattan & Alexander, 2021).…”
Section: Students' Individual Differences Influenced the Effectivenes...mentioning
confidence: 99%
“…However, prior knowledge needs to be activated to affect learning (Brod, 2021; Hattan & Alexander, 2021). One of the best-known examples of the effect of prior knowledge activation before exposure to text is Bransford and Johnson’s (1972) classic study.…”
Section: Reading To Learn From Multiple Textsmentioning
confidence: 99%